Psychiatric care for abnormal children at the Hospital Colônia Sant'Ana (Santa Catarina, Brazil, 1940s) A assistência psiquiátrica a crianças anormais no Hospital Colônia Sant’Ana (Santa Catarina, Brasil, 1940) - Borges V.T.* (2018)
Research into the psychiatric care for so-called abnormal children and youths in the Brazilian state of Santa Catarina is presented. The emergence of the idea of the "dangerous child" or the category of "minor" is discussed, drawing on Foucault's discussion of the notion of the "dangerous individual." This is followed by a presentation of the difficulties faced in the institutionalization of abnormal minors in the aforementioned state. The links between theories that enable so-called abnormal children to be identified and the ideas of eugenics are then questioned. Finally, the institutional dynamics involving so-called abnormal children admitted to the Hospital Colônia Sant'Ana in the 1940s are scrutinized.O artigo apresenta pesquisa centrada na assistência psiquiátrica destinada a crianças e jovens ditos anormais em Santa Catarina. Inicialmente, analisa-se o surgimento da ideia de “criança perigosa”, ou da categoria “menor”, a partir da discussão de Foucault sobre a noção de “indivíduo perigoso”, para então abordarem-se as dificuldades apresentadas na institucionalização da minoridade anormal em Santa Catarina. A seguir, são questionados os vínculos existentes entre as teorias que permitem identificar as crianças ditas anormais com as ideias eugênicas. Por fim, problematiza-se a dinâmica institucional que envolvia os menores ditos anormais internados no Hospital Colônia Sant’Ana na década de 1940.